Assessing Students’ Ability in Writing Argumentative Essay at an Indonesian Senior High School - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2020)
This research aims at finding out the students’ ability in writing argumentative essay at SMAN 1 Soe Kab. Timur Tengah Selatan NTT. The researcher will focus on evaluating the students’ writing ability in one aspect of writing namely mechanics. The researcher applied quantitative method and descriptive analysis design. The research was conducted in August 2017. This research was conducted at SMAN 1 Soe Kabupaten Timur Tengah Selatan NTT.. The population of this research was the eleventh grade students at SMAN 1 Soe Kabupaten Timur Tengah Selatan NTT in the 2018/2019 academic year. The number of population is 142 in four classes. The researcher took 5 students from each class as the sample of the research. Therefore, there were 20 students as sample. The test was used to find out the students’ ability in writing argumentative essay. In collecting data, the researcher asked the students to write an argumentative essay by choosing one of the give topics. To analyze the data, the researcher focused on evaluating the students’ writing in mechanics criteria. The result of the research shows that the students still have low ability in using mechanics in writing argumentative essay. The mean score of students is 2.45. In the students’ writing, most of the students got problem in: (1) The use of capital in the beginning of a sentence. Many of students still use small letter when they write the first letter in the beginning of a paragraph. (2)The students still use some capital letter in the middle of sentences. They write with capital letter in not appropriate position. (3) Some students still do not understand about the use of comma and point in a sentence.